Culture Shock dan Adaptasi Budaya Dosen CPNS Milenial di Universitas Palangka Raya - Pebrianti, Anisa (Universitas Merdeka Malang, 2024)
Palangka Raya University is one of the formation locations that is quite popular with candidates civil servant (CPNS) lecturers from outside the Central Kalimantan area. This research will observe the phenomenon of culture shock and lecturer adaptation Millennial CPNS from the Faculty of Social and Political Sciences, Palangka Raya University who come from outside the region will live and work long term in new placements. The new work placement location will certainly have various differences from their original location. This research uses a descriptive qualitative approach to interpret a phenomenon, data collection techniques using interview, observation and documentation techniques. Then it will be analyzed using four phases culture shock. Through this research, researchers found several results for the stages culture shock experienced and how to adapt to deal with it culture shock namely openness to getting to know culture and language, being able to understand the work environment, making social approaches with colleagues and the desire to adapt to local culture.